Economics of patenting a research tool: participation and productivity - Koo, Bonwoo; Wright, Brian D. (International Food Policy Research Institute, 2002)
When a new technology consists of sequences of innovations that culminate in a final consumer product, the balance between successive innovators is one of the main concerns in the design of the patent system. While intertemporal aspects of incentive are critical in this environment of sequential innovations, time plays a minor role in existing literature on dynamic models. By focusing on the incentives of follow-on innovators who commercialize an initial invention, this study examines the dynamic implications of the patent instrument (e.g., patent life) via a positive analysis. It shows that a long patent life may encourage innovation incentives and increase social welfare, contrary to existing arguments that argue that long patent life always discourages the incentive for subsequent innovations. This study also examines the implications of finite patent system in different market structures.